2014
DOI: 10.1111/jce.12500
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Isolation with a New Multipolar Irrigated Radiofrequency Ablation Catheter (nMARQ™): Feasibility, Acute and Short‐Term Efficacy, Safety, and Impact on Postablation Silent Cerebral Ischemia

Abstract: Background: Simultaneous multipolar ablation catheters have been proposed to simplify

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 16 publications
7
41
0
Order By: Relevance
“…The acute success rate found in this study and reported in recent studies using the novel nMARQ TM catheter [5] [7] [8] compares with the acute success rate reported by previous studies using a conventional, single-tip approach guided by a 3D mapping system [9], cryoballoon [3], a visually guided laser balloon catheter [10], or PVAC [4].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The acute success rate found in this study and reported in recent studies using the novel nMARQ TM catheter [5] [7] [8] compares with the acute success rate reported by previous studies using a conventional, single-tip approach guided by a 3D mapping system [9], cryoballoon [3], a visually guided laser balloon catheter [10], or PVAC [4].…”
Section: Discussionsupporting
confidence: 60%
“…Overall, 100% targeted PVs could be isolated without procedure-related complications. In other study 25 patients with PAF underwent PVI using the nMARQ TM catheter [7]. The ablation was guided by electroanatomic map created by nMARQ TM and merged with the 3-D magnetic resonance imaging (MRI) shell of LA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deneke et al (7,13) reported one esophago-pericardial fistula, a high incidence of mild thermal esophageal lesions, and an incidence of silent cerebral lesions higher than single-tip irrigated RF. However Scaglione et al (12), using a specific and cautious procedural workflow, observed the complete absence of periprocedural silent cerebral ischemia. In our series no stroke/TIA, pericardial effusion, or cardiac tamponade were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on the follow-up. In the Scaglione et al (12) series 17/25 (68%) patients with paroxysmal AF were free from AF without antiarrhythmic drugs at a 6-month follow-up; in the Shin et al (10) series, after 3 months, sinus rhythm was stable off antiarrhythmic drugs in 17 of 21 (80.9%) patients; in the Zellerhof et al (11) series single and multiple procedure success rates during a mean follow-up of 140+75 days were 66 and 77%, respectively. In our cohort the freedom of atrial arrhythmias was similar at a longer follow-up (13.9 months) and also patients with persistent AF showed a recurrence rate of 30%.…”
Section: Discussionmentioning
confidence: 99%